Gene‐centric approach identifies new and known loci for FVIII activity and VWF antigen levels in European Americans and African Americans. Issue 6 (1st April 2015) - Tang, Weihong; Cushman, Mary; Green, David; Rich, Stephen S.; Lange, Leslie A.; Yang, Qiong; Tracy, Russell P.; Tofler, Geoffrey H.; Basu, Saonli; Wilson, James G.; Keating, Brendan J.; Weng, Lu‐Chen; et al.
<x xml:space="preserve">Abstract</x> Coagulation factor VIII and von Willebrand factor (VWF) are key proteins in procoagulant activation. Higher FVIII coagulant activity (FVIII:C) and VWF antigen (VWF:Ag) are risk factors for cardiovascular disease and venous thromboembolism. Beyond associations with ABO blood group, genetic determinants of FVIII and VWF are not well understood, especially in non European‐American populations. We performed a genetic association study of FVIII:C and VWF:Ag that assessed 50, 000 gene‐centric single nucleotide polymorphisms (SNPs) in 18, 556 European Americans (EAs) and 5, 047 African Americans (AAs) from five population‐based cohorts. Previously unreported associations for FVIII:C were identified in both AAs and EAs with KNG1 (most significantly associated SNP rs710446, Ile581Thr, P = 5.10 × 10−7 in EAs and P = 3.88 × 10−3 in AAs) and VWF rs7962217 (Gly2705Arg, P = 6.30 × 10−9 in EAs and P = 2.98 × 10−2 in AAs). Significant associations for FVIII:C were also observed with F8/TMLHE region SNP rs12557310 in EAs (P = 8.02 × 10−10), with VWF rs1800380 in AAs (P = 5.62 × 10−11), and with MAT1A rs2236568 in AAs (P = 1.69 × 10−6). We replicated previously reported associations of FVIII:C and VWF:Ag with the ABO blood group, VWF rs1063856 (Thr789Ala), rs216321 (Ala852Gln), and VWF rs2229446 (Arg2185Gln). Findings from this study expand our understanding of genetic influences for FVIII:C and VWF:Ag in both EAs and AAs. Am. J. Hematol. 90:534–540, 2015. © 2015 Wiley Periodicals, Inc.